Remote Sensing Retrieval of Isoprene Concentrations in the Southern Ocean. Issue 13 (1st July 2020) - Rodríguez‐Ros, Pablo; Galí, Martí; Cortés, Pau; Robinson, Charlotte Mary; Antoine, David; Wohl, Charel; Yang, MingXi; Simó, Rafel
Abstract: Isoprene produced by marine phytoplankton acts as a precursor of secondary organic aerosol and thereby affects cloud formation and brightness over the remote oceans. Yet the marine isoprene emission is poorly constrained, with discrepancies among estimates that reach 2 orders of magnitude. Here we present ISOREMS, the first satellite‐only based algorithm for the retrieval of isoprene concentration in the Southern Ocean. Sea surface concentrations from six cruises were matched with remotely sensed variables from MODIS Aqua, and isoprene was best predicted by multiple linear regression with chlorophyll a and sea surface temperature. Climatological (2002–2018) isoprene distributions computed with ISOREMS revealed high concentrations in coastal and near‐island waters, and within the 40–50°S latitudinal band. Isoprene seasonality paralleled phytoplankton productivity, with annual maxima in summer. The annual Southern Ocean emission of isoprene was estimated at 63 Gg C yr −1 . The algorithm can provide spatially and temporally realistic inputs to atmospheric and climate models. Plain Language Summary: Isoprene is a marine trace gas with climatic relevance in remote regions of the ocean, because it reacts readily in the atmosphere to produce aerosols (atmospheric particles) that make clouds brighter. In the Southern Ocean, however, its regional emission is poorly quantified. We explored the capability of satellite observations (MODIS Aqua, NASA) to reconstruct isoprene concentrations measured in the Southern Ocean during various oceanographic cruises. We found an empirical relationship between isoprene and sea surface chlorophyll and temperature and used it to produce regional maps of isoprene emission. The new tool presented here, named ISOREMS, enables detailed exploration of the role of ocean‐leaving isoprene in the Southern Ocean atmosphere. Key Points: We present an algorithm for the retrieval of isoprene concentrations in the Southern Ocean from remote sensing Isoprene peaks in midsummer and is highest in coastal and near‐island waters and in the 40–50°S latitudinal band The annual isoprene emission from the entire Southern Ocean amounts 63 Gg C yr −1